Striatal and extrastriatal dopamine transporter in cannabis and tobacco addiction: a high-resolution PET study - Leroy, Claire; Karila, Laurent; Martinot, Jean-Luc; Lukasiewicz, Michaël; Duchesnay, Edouard; Comtat, Claude; Dollé, Frédéric; Benyamina, Amine; Artiges, Eric; Ribeiro, Maria-Joao; Reynaud, Michel; Trichard, Christian (Addiction biology, 2012)
ABSTRACT The dopamine (DA) system is known to be involved in the reward and dependence mechanisms of addiction. However, modifications in dopaminergic neurotransmission associated with long‐term tobacco and cannabis use have been poorly documented in vivo. In order to assess striatal and extrastriatal dopamine transporter (DAT) availability in tobacco and cannabis addiction, three groups of male age‐matched subjects were compared: 11 healthy non‐smoker subjects, 14 tobacco‐dependent smokers (17.6 ± 5.3 cigarettes/day for 12.1 ± 8.5 years) and 13 cannabis and tobacco smokers (CTS) (4.8 ± 5.3 cannabis joints/day for 8.7 ± 3.9 years). DAT availability was examined in positron emission tomography (HRRT) with a high resolution research tomograph after injection of [11C]PE2I, a selective DAT radioligand. Region of interest and voxel‐by‐voxel approaches using a simplified reference tissue model were performed for the between‐group comparison of DAT availability. Measurements in the dorsal striatum from both analyses were concordant and showed a mean 20% lower DAT availability in drug users compared with controls. Whole‐brain analysis also revealed lower DAT availability in the ventral striatum, the midbrain, the middle cingulate and the thalamus (ranging from −15 to −30%). The DAT availability was slightly lower in all regions in CTS than in subjects who smoke tobacco only, but the difference does not reach a significant level. These results support the existence of a decrease in DAT availability associated with tobacco and cannabis addictions involving all dopaminergic brain circuits. These findings are consistent with the idea of a global decrease in cerebral DA activity in dependent subjects.